No Association between Elevated Total Homocysteine Levels and Functional Outcome in Elderly Patients with Acute Cerebral Infarction - Wang, Wanjun; Gao, Chunlin; Yu, Changshen; Liu, Shoufeng; Hou, Dongzhe; Wang, Yajing; Wang, Chen; Mo, Lidong; Wu, Jialing (Frontiers in Aging Neuroscience, 2017)
Background: An elevated plasma total homocysteine (tHcy) level is an independent risk factor for vascular events. The aim of the present study was to investigate the association between tHcy levels in the acute phase of cerebral infarction and functional outcome among elderly patients. Methods: Between October 2009 and December 2012, we recruited 594 elderly patients (age >75) with first-onset acute cerebral infarction who were consecutively admitted to the Department of Neurology of Tianjin Huanhu Hospital, China. Levels of tHcy and other biochemical values were measured within 24 h after admission. tHcy values were classiﬁed according to quartiles (<9.94; 9.94 to <12.7; 12.7 to <16.8; and ≥16.8 µmol/L). We examined the relationship between tHcy levels at admission and modified Rankin Scale scores (mRS) using univariate and multivariate analyses. Patients were followed up at 3 months and 1 year after stroke. Results: Within 3 months after stroke, 64 patients died, 37 had recurrent ischemic stroke, and 22 were lost to follow-up; thus, 471 patients were reviewed and analyzed. By the time of the 1-year follow-up, an additional 48 patients had died, 44 had recurrent ischemic stroke, and 40 had been lost to follow-up; the remaining 339 patients were thus reviewed and analyzed. Elevated tHcy levels were not associated with functional outcome among elderly patients with acute cerebral infarction (p >0.05). Only the National Institutes of Health Stroke Scale score was associated with a poor outcome after adjusting for confounders at 3 months and 1 year (adjusted odds ratio, 1.38; 95% CI, 1.28–1.49; p <0.01; adjusted odds ratio, 1.34; 95% CI, 1.25–1.44; p < 0.01, respectively). Conclusions: Among elderly patients with acute cerebral infarction, elevated tHcy at admission was not a predictive factor of outcome at 3 months and 1 year after stroke onset.